A detailed insight into anion sensing based on intramolecular charge transfer (ICT) mechanism: A comprehensive review of the years 2016 to 2021 - Pal, Adwitiya; Karmakar, Manisha; Bhatta, Sushil Ranjan; Thakur, Arunabha (Coordination chemistry reviews, 2021)
•First review in the recent time focusing on the anion sensing based on ICT mechanism.•A list of 123 probes and their different sensing parameters are described.•Categorical representation of probes based on number and type of anion recognized.•An overview of the design strategies and their corresponding molecular systems.•Some perspectives on the challenges and opportunities in this area are discussed. Anion detection and quantification remain always challenging due to their inherent strong hydration energy, complex geometries and pH dependence. Several techniques and methodologies have been developed for the recognition and sensing of anions. Among all such techniques, fluorescence spectroscopy has received special attention due to its highly convenient and accurate detection capacity. A number of different mechanisms are prevalent in the literature for the emission spectroscopy. Intramolecular charge transfer (ICT) is one of such predominant mechanisms, which is usually observed in molecules with D-π-A or D-A type of structural arrangement. When ICT based probes interact with the desired analyte, the electron density in the recognition group is altered (e.g., as a result of bond cleavage, substitution, or substrate coordination) which installs a ‘push-pull’ system in the molecule. In the past two decades, a huge number of publications have emerged on this topic. Keeping into account the vast number of reports on anion sensing relied upon ICT mechanism, we will confine our discussion to sensors that are developed in last 6 years. The structural features of all the selected probes (total 123 probes), developed in the last 6 years, will be discussed in the present review with the particular emphasis on the mechanism (ICT) responsible for the detection and recognition of various anions. Apart from the mechanistic details, information about the detection limit, selectivity and visible change of color/state, binding units and stoichiometries with anions have also been discussed thoroughly and collected in tabular format. For the sake of legibility, all the probes have been categorized according to the number of anions they detect and are subdivided into specific anion-based sensing and their mechanism. This review aims to be a comprehensive, convincing and reader-friendly review of general interest to the chemistry community. To the best of our knowledge, this is the first survey in the contemporary time to cover the complete literature of past six years about anion sensing exclusively based on ICT mechanism. Throughout the review we provide an illustrative overview about the design strategies that may be exploited for analyte sensing and their corresponding suitable molecular systems. We hope, this review will enhance the basic understanding of the subject of ICT based mechanism which will certainly help the researchers to generate new molecular architectures with superior anion sensing ability in future.